ANALISA RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING DAN CAPITAL SEBAGAI ALAT UNTUK MENGUKUR TINGKAT KESEHATAN BANK : STUDI KASUS PADA BANK PEMERINTAH YANG TERDAFTAR DI BEI TAHUN 2011-2013 - Hamta, Firdaus (Universitas Riau Kepulauan, 2014)
This study aims to determine the soundness of government banks listed on the Stock Exchange in the period 2011-2013 by using the method of valuation of the bank is the method of Risk - Based Bank Rating ( RBBR ) in accordance with the Circular Letter No. 13/24 / DPNP October 25, 2011 which is described by RGEC. RGEC consists of Aspects Risk (Risk), Aspects of Good Corporate Governance (GCG ), Aspects of Earnings and Aspect Capital . This study was a descriptive study quantitatively by calculating the ratio existing in the aspect of risk (LDR and NPL ), aspects of GCG ( ROE and NPM ), aspects of earnings ( ROA and NIM ), and aspects of capital ( CAR ). This study uses data publication of annual financial statements of state banks listed on the Stock Exchange from 2011 to 2013 , namely PT . Bank Mandiri , PT . Bank Rakyat Indonesia , PT . Bank Negara Indonesia and PT . State Savings Bank . It can be concluded that the performance of state -owned commercial banks in good shape . This is evident from the calculated ratio is in accordance with the provisions stipulated by Bank Indonesia . Based on the research that has been done that overall during the 2011-2013 four state-owned commercial banks have a healthy level of health